CA19-9-related macrophage polarization drives poor prognosis in HCC after immune checkpoint inhibitor treatment - Du, Tingting; Zou, Jialin; Yang, Yunying; Xie, Honghui; Pang, Hui; Zhuang, Wenquan; Wang, Shutong; Wei, Guangyan (Frontiers in Oncology, 2025)
BackgroundElevated levels of carbohydrate antigen 19-9 (CA19-9) levels are known to worsen outcomes in various tumors by influencing immune responses. However, the role of CA19-9 in immunotherapy for hepatocellular carcinoma (HCC) remains poorly understood.MethodsThis study included 621 patients treated with anti-PD-1/PD-L1 treatment at the First Affiliated Hospital of Sun Yat-sen University from January 2017 to March 2023. During immunotherapy, CA19-9 levels were measured and classified as either elevated (≥35 U/mL) or normal (<35 U/mL) for clinical analysis.ResultsPatients with elevated CA19-9 levels had significantly worse progression-free survival (PFS) and overall survival (OS). The 1-year and 2-year PFS rates were 53.3% and 29.1% in the normal CA19-9 group compared to 16.9% and 11.3% in the elevated group (p < 0.001). Similarly, the 1-year and 2-year OS rates were 90.5% and 75.5% in the normal group versus 64.0% and 36.5% in the elevated group (p < 0.001). Multivariate analysis confirmed CA19-9 was an independent prognostic factor for both PFS and OS. Bioinformatic analysis indicated that FUT3, a key gene in CA19-9 synthesis, correlated with increased macrophage infiltration. And increased M2 macrophage levels and reduced M1 macrophage levels were noted in HCC samples with elevated CA19-9 levels. Further in vivo experiments indicated blocking CA19-9 improved the efficacy of PD-1 treatment through inducing the M1-like polarization of macrophages.ConclusionsOur findings demonstrate that elevated CA19-9 levels during immunotherapy are associated with poor survival outcomes in HCC patients. These findings highlight the crucial role of CA19-9 in shaping the tumor immune environment, particularly through its effect on macrophage polarization, and suggest that targeting CA19-9 may improve immunotherapy outcomes.